2016
DOI: 10.1155/2016/9364170
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Platelet-Rich Plasma as Biological Augmentation for Acute Achilles Tendon Rupture Repair

Abstract: Acute Achilles tendon rupture is one of the most common tendon injuries in adults. We hypothesized that Platelet-Rich Plasma (PRP) can be used as biological augmentation for surgical treatment of acute Achilles tendon rupture. Our study is a prospective randomized controlled trial. Patients with acute Achilles tendon rupture undergoing surgical repair were randomly assigned into either control group or PRP group. End-to-end modified Krackow suture was performed in both groups. In the PRP group, PRP was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
2
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 23 publications
2
75
2
25
Order By: Relevance
“…Another prospective randomized controlled study found less functional outcomes in dogs treated with PRP and surgery compared with those treated with surgery alone; however, in this study the platelet concentration was 17 times that of whole blood in contrast to most commercially available systems that result in concentrations between 1 and 8 times whole blood in dogs . In a randomized controlled prospective clinical trial comparing surgical repairs of human Achilles tendon ruptures with and without PRP, there were improved short and midterm functional outcomes in the patients treated with PRP on the basis of isokinetic muscle strength, ankle range of motion, and muscle mass . In a more recent prospective randomized study, there were no improvements in outcomes with PRP combined with surgical repair in 30 dogs with CCT ruptures .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Another prospective randomized controlled study found less functional outcomes in dogs treated with PRP and surgery compared with those treated with surgery alone; however, in this study the platelet concentration was 17 times that of whole blood in contrast to most commercially available systems that result in concentrations between 1 and 8 times whole blood in dogs . In a randomized controlled prospective clinical trial comparing surgical repairs of human Achilles tendon ruptures with and without PRP, there were improved short and midterm functional outcomes in the patients treated with PRP on the basis of isokinetic muscle strength, ankle range of motion, and muscle mass . In a more recent prospective randomized study, there were no improvements in outcomes with PRP combined with surgical repair in 30 dogs with CCT ruptures .…”
Section: Discussionmentioning
confidence: 59%
“…32 In a randomized controlled prospective clinical trial comparing surgical repairs of human Achilles tendon ruptures with and without PRP, there were improved short and midterm functional outcomes in the patients treated with PRP on the basis of isokinetic muscle strength, ankle range of motion, and muscle mass. 33 In a more recent prospective randomized study, there were no improvements in outcomes with PRP combined with surgical repair in 30 dogs with CCT ruptures. 34 Conclusions regarding the potential benefits of PRP in the treatment of canine CCT ruptures cannot be determined from the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Published data are mixed with fewer robust studies for Achilles and patella tendinopathy, limiting our ability to draw conclusions about efficacy. Table 2 presents a list of studies [49‐89] and levels of evidence.…”
Section: Common Regenerative Methodsmentioning
confidence: 99%
“…Zou y colaboradores realizó un estudio aprobado por el comité ético de del Sexto Hospital Popular de Shanghai (53). Reclutaron 52 casos de roturas agudas de Aquiles durante el período de estudio.…”
Section: ¿Plasma Rico En Plaquetas Para La Recuperación Del Tendón Deunclassified